Trying : a loving guide to navigating the emotions of infertility and loss - Martin, Alessa; Swenson, Liz (Familius, 2026)
"After the confirmation of pregnancy, a woman receives recommendations and resources for the journey she is about to begin. After a diagnosis of unexplained infertility, miscarriage, or a failed fertility round, a woman might receive additional suggestions for medical intervention. But what she rarely, if ever, receives are any tools to help her cope with what she is experiencing. Enter Trying, an illustrated guide that's like a life raft on the sea of your infertility journey. The condition of 'trying' is a hard and harrowing journey in which people can experience loss, grief, shame, and confusion. Often quietly. Trying: A Loving Guide to Navigating the Emotions of Infertility and Loss holds space for the grief and pain while also offering love, support, stories, and practical strategies from people who have been there before. Whether you are still trying, have stopped trying, are considering adoption or surrogacy, or are anywhere in between, there's a story here for you. Accompanied by stunning illustrations that make the advice easy to digest, this bite-size companion will empower you to keep braving wind-tossed seas. Wherever your journey leads, you are seen, you are heard, and you are not alone."--Abramsbooks.com.